PAREMEOLOGICAL WORLD VIEW OF ITALIAN SPEAKERS - Гольцева, М. І. (Studia Philologica, 2019)
In the proposed research, the analysis of paremiological picture of the world of Italian language is performed; the notions of “picture of the world”, “linguistic picture of the world”, “paremiological picture of the world” are analyzed; the connection between the linguistic and paremiological picture of the world is distinguished; the frequency of using mythological proverbs with the proper name is set. According to the conducted research, it is possible to distinguish the following notions : 1) picture of the world is the way people see this world, how they communicate with each other, etc.; 2) linguistic picture of the world deals with the linguistic approach in seeing the world, how with the help of words people express their feelings towards different things; 3) paremiological picture of the world deals with proverbs and sayings, with the help of which people show their attitude to different things. As a result, it is possible to notice that this research of proper names in Italian proverbs in the paremiological picture of the world promotes reconstruction of one of important components of a national language picture of the world which is a cultural sphere of any language. We have distinguished that proverbs and sayings with the proper name are mythological, religious, historical, literal, toponymic, from various spheres of social and individual activity of native speakers. As a result, in the studied proverbs and sayings the features connected with mythology come to the first place among the rest of them. Never before have the scientists studied proper names in the light of meaning and form. While investigating proverbs with proper names it is possible to notice the link between ancient myths and modern mass media where we have found the majority of our examples during the research. And it is noticed that the majority of analyzed proverbs in mass media have examples in political and economic articles. From the studied proverbs and sayings we can make the conclusion that it is a vital source of national and cultural wisdom that is worth analyzing.